2019
DOI: 10.1523/eneuro.0079-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Valence-Dependent Coupling of Prefrontal-Amygdala Effective Connectivity during Facial Affect Processing

Abstract: Despite the importance of the prefrontal-amygdala (AMY) network for emotion processing, valence-dependent coupling within this network remains elusive. In this study, we assessed the effect of emotional valence on brain activity and effective connectivity. We tested which functional pathways within the prefrontal-AMY network are specifically engaged during the processing of emotional valence. Thirty-three healthy adults were examined with functional magnetic resonance imaging while performing a dynamic faces a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 87 publications
2
23
0
2
Order By: Relevance
“…Additionally, we found a significant difference between the fearful and sad associated connectivity from the amygdala to dlPFC. Overall, the pattern of connectivity observed here is generally consistent with previous investigations of implicit processing of negative expressions, particularly those findings concerning the connectivity from the amygdala to dlPFC and vmPFC to amygdala (Vai et al, 2015;Willinger et al, 2019). While we did not observe the significant modulation from the dlPFC to amygdala reported in the study by Vai et al (2015), this was likely because of their indirect interaction via the vmPFC in our model.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, we found a significant difference between the fearful and sad associated connectivity from the amygdala to dlPFC. Overall, the pattern of connectivity observed here is generally consistent with previous investigations of implicit processing of negative expressions, particularly those findings concerning the connectivity from the amygdala to dlPFC and vmPFC to amygdala (Vai et al, 2015;Willinger et al, 2019). While we did not observe the significant modulation from the dlPFC to amygdala reported in the study by Vai et al (2015), this was likely because of their indirect interaction via the vmPFC in our model.…”
Section: Discussionsupporting
confidence: 92%
“…Given their roles, the interaction between the dlPFC and amygdala, depending on the directionality, may be important in directing conscious awareness toward and regulating emotional responses to salient emotional stimuli ( Dolcos et al, 2006 ; Banks et al, 2007 ; Costafreda et al, 2008 ; Etkin et al, 2015 ). Despite this, previous research examining the directionality of these interactions has not examined whether facial expressions with differing arousal ratings, such as fearful and sad expressions, differently modulate this relationship ( Sladky et al, 2015 ; Vai et al, 2015 ; Willinger et al, 2019 ). The sparse anatomic connectivity between these regions additionally suggests that the regulatory role of the dlPFC on the amygdala is likely dependent on interactions with mediatory regions including the vmPFC ( Phillips et al, 2003 ; Ray and Zald, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that these two circuits regulate general emotional states rather than specifically affecting social behaviors. Interestingly, human neuroimaging studies showed that connectivity from mPFC to amygdala is modulated by both positive and negative valence, whereas the inverse connection (BLA-mPFC) is affected only by positive valence ( Willinger et al, 2019 ). In the case of the PL-BLA circuit, our data suggest that its activation creates a negative emotional state that is sufficient to promote avoidance and leads to a lack of social preference.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation of our results is that competition for accessing the working memory system could depend upon a dichotomic evaluation between what is endowed with an emotional valence and what is not (emotional vs. non-emotional), independently from the “ valence direction ” (negative or positive). Recently, Willinger et al (2019) performed an fMRI analysis during an emotional face-matching task and found that the processing of valence directly induces changes in the strength of the bidirectional coupling within a prefrontal-amygdala circuitry (Willinger et al, 2019). Moreover, Kensinger and Schacter (2006) found that independent brain networks specifically processed either positive or negative stimuli.…”
Section: Discussionmentioning
confidence: 99%